2010
DOI: 10.1080/10599241003627110
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Livestock-Associated MRSA in Agriculture

Abstract: Researchers, veterinary and health care practitioners, and agricultural producers gathered in Johnston, Iowa, to attend the eighth annual Midwest Rural Agricultural Safety and Health Forum (MRASH), November 2009. Among several focus areas, four plenary talks were given on the current research being conducted examining methicillin-resistant Staphylococcus aureus (MRSA) on swine farms in the United States. These focused on prevalence of MRSA on farms, both in swine and in human workers; the presence of MRSA in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…MRSA has been previously detected in air samples (15,33,38). In the present study, air samples were MRSA positive on only day 1 p.i.…”
Section: Discussionsupporting
confidence: 50%
“…MRSA has been previously detected in air samples (15,33,38). In the present study, air samples were MRSA positive on only day 1 p.i.…”
Section: Discussionsupporting
confidence: 50%
“…number of other studies have reported a prevalence of MRSA in RP products ranging from as low as 2 to 45% (de Boer et al 2009;Harper et al 2010;Beneke et al 2011;Buyukcangaz et al 2013;Lassok and Tenhagen 2013). The presence of MRSA in RP could be due to survival of strains resistant to the temperatures during scalding, singeing, hot wash, pasteurization and refrigeration, or to cross-contamination from other products, environments (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…They collected a smaller air volume (100 liters versus Ͼ300 liters in our study) and used impaction instead of filtration and impingement for sampling. Impaction has been successfully used for MRSA detection in pig barns before (30), but its specific sensitivity for MRSA has not been compared to the sensitivities of the two sampling methods used in our study. In contrast to the results of a previous study carried out on pig farms (19), there was no significant difference between the results for the two air sampling methods in this study.…”
Section: Discussionmentioning
confidence: 99%